Spatial distribution of erosion and deposition zones as a result of surface runoff based on probability model. A case study in the island of Samos. - Kotinas, V.; Gournelos, Th.; Evelpidou, N.; Vlachogiorgou, M. (SGE2015, 2015)
In this paper we attempt to map erosion and deposition zones in the island of Samos (Greece). The relief of Samos is characterized by hilly and mountainous geomorphology mantled by surface sediments and soils. The processes of erosion depends mainly on the frequency and magnitude of precipitation, surface water flow, slope characteristics, rock’s susceptibilitiy to erosion, vegetation and human impacts. The aim of this paper is to study these dynamic processes using easily updated spatial mapping processes in order to design structures to minimize erosion.